First photon-counting detector computed tomography in the living crocodile: a 3D-Imaging study with special reference to amphibious hearing - Melkersson, Karl-Gunnar; Li, Hao; Rask-Andersen, Helge (Frontiers in Cell and Developmental Biology, 2024)
Background: Crocodiles are semi-aquatic animals well adapted to hear both on land and under water. Currently, there is limited information on how their amphibious hearing is accomplished. Here, we describe, for the first time, the ear anatomy in the living crocodile using photon-counting detector computed tomography (PCD-CT) and 3D rendering. We speculate on how crocodiles, despite their closed ear canals, can use tympanic hearing in water that also provides directional hearing Material and Methods: A Cuban crocodile (Crocodylus rhombifer) underwent photon-counting detector computed tomography (PCD-CT), under anesthesia and spontaneous respiration. In addition two seven-month-old C. rhombifer and a juvenile Morelet´s crocodile (Crocodylus moreletii) underwent micro-computed tomography (µCT) and endoscopy. One adult Cuviérs dwarf caiman (Paleosuchus palpebrosus) was micro-dissected and video-recorded. Aeration, earflap, and middle ear morphology were evaluated and compared after 3D modeling. Results and Discussion: PCD-CT and µCT with 3D rendering and segmentation demonstrated the anatomy of the external and middle ears with high resolution in both living and expired crocodiles. Based on the findings and comparative examinations, we suggest that the superior earflap, by modulating the meatal recess together with local bone conduction, may implement tympanic hearing in submerged crocodiles, including directional hearing.